Do fences make good neighbours? Evidence from an insurgency in India - Heidi Kaila; Saurabh Singhal; Divya Tuteja (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
India has employed a variety of military, political, and economic measures to combat the long running insurgency in Kashmir with little evidence on what contributes to stability in the region. This paper uses a variety of tests to detect structural breaks in the time series for violence over the period 1998-2014. We identify a transition from a high violence regime to a low violence regime that coincides with (i) the fencing of the border with Pakistan (ii) the implementation of a large-scale development programme, and (iii) the phasing in of the Indian National Rural Employment Guarantee Scheme (NREGS). Our results highlight the complementary roles of development programmes and security in reducing violence.
Keywords: C22; D74; F51; 330; conflict; multiple structural breaks; Nonlinear Time Series Models; Jammu; Kashmir; India